Empire of sacrifice: the religious origins of American violence - Pahl, Jon (New York University Press, 2010)
It is widely recognized that American culture is both exceptionally religious and exceptionally violent. Americans participate in religious communities in high numbers, yet American citizens also own guns at rates far beyond those of citizens in other industrialized nations. Since9/11, United States scholars have understandably discussed religious violence in terms of terrorist acts, a focus that follows United States policy. Yet, according to Jon Pahl, to identify religious violence only with terrorism fails to address the long history of American violence rooted in religion throughout the co